2017
DOI: 10.3390/ijerph14040385
|View full text |Cite
|
Sign up to set email alerts
|

How Does Ambient Air Temperature Affect Diabetes Mortality in Tropical Cities?

Abstract: Diabetes is well-known as one of the many chronic diseases that affect different age groups. Currently, most studies that evaluated the effects of temperature on diabetes mortality focused on temperate and subtropical settings, but no study has been conducted to assess the relationship in a tropical setting. We conducted the first multi-city study carried out in tropical cities, which evaluated the temperature–diabetes relationship. We collected daily diabetes mortality (ICD E10–E14) of four Philippine cities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
4
23
0
Order By: Relevance
“…A total of 40 articles and grey literature were found eligible for this review. Only 34 quantitative studies were presented here [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 40 articles and grey literature were found eligible for this review. Only 34 quantitative studies were presented here [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Among the time-series studies, six (22%) simply visualized patterns from time-series plots [28,31,39,40,43,47], while the rest used a variety of statistical models. Eight (30%) used general linear models (i.e., simple and multiple linear regressions) [27,32,34,35,38,41,44,45], eight (30%) used generalized linear models (e.g., quasi-poisson/poisson models and distributed lag nonlinear models) [15,19,22,25,33,36,42], two (7%) used autoregressive models (i.e., autoregressive integrated moving average models and seasonal autoregressive integrated moving average models) [37,44], two (7%) used wavelet analysis [16,20], and four (15%) used other kinds of models (i.e., general additive model [14,15], spectral analysis [18], dynamic linear model [16], and transfer entropy [46]). The temporal resolutions used in the time-series studies were daily (19%, 5/27), weekly (15%, 4/27), monthly (63%, 17/27), and annual (7%, 2/27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-linear models have been widely used in assessing the relationships between meteorological factors and health outcomes (Peng et al, 2017;Wang et al, 2017). Meanwhile, most studies found the lagged effects of meteorological factors (Antunes et al, 2017;Seposo et al, 2017). Therefore, some researchers adopted distributed lag non-linear model (DLNM) to assess the non-linear effects of meteorological factors and the lagged effects simultaneously (Gasparrini, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A worldwide meta-regression study found a positive association between glucose intolerance and outdoor temperature [ 9 ]. Studies from the United States [ 2 4 ] and Sydney, Australia [ 5 ] found positive associations between temperature and DM-related complications and mortality, while studies from the Philippines [ 6 ] and China [ 7 , 8 ] found increased DM mortality at both high and low temperatures. Climate change, which is leading to higher average global temperatures [ 10 ], and the rising prevalence of DM have been suggested to pose a “dual threat” in increasing the disease burden [ 11 ].…”
Section: Introductionmentioning
confidence: 99%